2020
DOI: 10.1101/2020.09.02.279125
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A mesh microelectrode array for non-invasive electrophysiology within neural organoids

Abstract: Organoids are emerging in vitro models of human physiology. Neural models require the evaluation of functional activity of single cells and networks, which is best measured by microelectrode arrays. The characteristics of organoids clash with existing in vitro or in vivo microelectrode arrays. With inspiration from implantable mesh electronics and growth of organoids on polymer scaffolds, we fabricated suspended hammock-like mesh microelectrode arrays for neural organoids. We have demonstrated the growth of or… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…11 Two-dimensional (2D) microelectrode arrays (MEAs) have been used to interface with neuronal organoids but exhibit a limited 2D interface with the organoid. [12][13] Optical techniques, such as functional Ca 2+ imaging, which provide high spatial resolution and throughput, lack the temporal precision of ephys techniques (msec resolution), required to study the temporal dynamics of neural activity. 14 Here, we present a platform consisting of a 3D self-rolled biosensor array (3D-SR-BA) 15 that wraps around the 3D structure of a rat cortical spheroid.…”
Section: Introductionmentioning
confidence: 99%
“…11 Two-dimensional (2D) microelectrode arrays (MEAs) have been used to interface with neuronal organoids but exhibit a limited 2D interface with the organoid. [12][13] Optical techniques, such as functional Ca 2+ imaging, which provide high spatial resolution and throughput, lack the temporal precision of ephys techniques (msec resolution), required to study the temporal dynamics of neural activity. 14 Here, we present a platform consisting of a 3D self-rolled biosensor array (3D-SR-BA) 15 that wraps around the 3D structure of a rat cortical spheroid.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work shows great promise, e.g., a 3D flexible MEAplatform, which was able to form a three-dimensional interface to a brain model including both astrocytes and neurons in a hydrogel matrix (Soscia et al 2020). McDonald et al showed how a flexible mesh-like MEA-array can be used to interface brain organoids (McDonald et al 2021).…”
Section: Advanced Sensors For Studying Neuro-coagulationmentioning
confidence: 99%
“…Electrical measurement techniques such as 2D microelectrode arrays (MEA) 15,16 and patch-clamp 17,18 have been applied to measure the functional development of brain organoids, but they can only capture the activities from the bottom surface of brain organoids [19][20][21] or assay one cell at a time with cell membrane disruption. The recent development of 3D bioelectronics enables 3D interfaces with brain organoids 1,19,[21][22][23][24][25] . However, they can only contact organoids at the surface by flexible electronics or penetrate organoids invasively by rigid probes, which cannot further accommodate volume and morphological changes of brain organoids during development.…”
Section: Introductionmentioning
confidence: 99%